Prognostic factors and survival outcomes in patients with salivary duct carcinoma: a retrospective cohort study - Fei Chen; Liangbo Li; Jingqiao Tao; Nenghao Jin; Liwei Wang; Liang Zhu; Bo Qiao; Lejun Xing; Bo Wei; Jingqiu Bu; Haizhong Zhang (BMC Oral Health)
Abstract Background Salivary duct carcinoma (SDC) is a highly aggressive salivary gland malignancy with poor prognosis. The aim was to investigate the prognostic factors and survival outcomes in a cohort of SDC patients. Materials and methods This study retrospectively analyzed the clinicopathological data of 61 SDC patients treated at the First Medical Center of the PLA General Hospital between January 2010 and December 2020. Univariate and multivariate Cox proportional hazards models were used to identify prognostic factors for overall survival (OS). Fine-Gray subdistribution hazard model was used to analyze prognostic factors for cancer-specific mortality. Results Of the 61 patients, the parotid gland was the most common primary site (70.5%). Lymph node and distant metastases were present in 35 (57.4%) and 23 (37.7%) patients, respectively. The 5-year and 3-year OS rates were 35.2% and59.7%. Multivariate analysis identified platelet count (HR 0.99, 95%CI 0.98–1.00, P = 0.011) and distant metastasis (HR 2.79, 95%CI 1.38–5.64, P = 0.004) as independent prognostic factors for OS. Lymph node metastasis (SHR = 2.18, 95%CI 1.05–4.52, P = 0.036), distant metastasis (SHR = 3.07, 95%CI 1.47–6.42, P = 0.003), and platelet count (SHR = 0.99, 95%CI 0.99–1.00, P = 0.041) were independent prognostic factors for cancer-specific mortality. Conclusions Distant metastasis and thrombocytopenia are important predictors of poor overall survival in SDC patients. These findings underscore the potential significance of incorporating hematological parameters and metastatic status into clinical decision-making to optimize risk stratification and personalized treatment strategies.